Chemical Signals of Synthetic Disaccharide Derivatives Dominate Rhamnolipids at Controlling Multiple Bacterial Activities. Issue 1 (19th November 2015) - Singh, Nischal; Shetye, Gauri S.; Zheng, Hewen; Sun, Jiayue; Luk, Yan‐Yeung
Abstract: Microbes secrete molecules that modify their environment. Here, we demonstrate a class of synthetic disaccharide derivatives (DSDs) that mimics and dominates the activity of naturally secreted rhamnolipids by Pseudomonas aeruginosa . The DSDs exhibit the dual function of activating and inhibiting the swarming motility through a concentration‐dependent activity reversal that is characteristic of signaling molecules. Whereas DSDs tethered with a saturated farnesyl group exhibit inhibition of both biofilm formation and swarming motility, with higher activities than rhamnolipids, a saturated farnesyl tethered with a sulfonate group only inhibits swarming motility but promote biofilm formation. These results identified important structural elements for controlling swarming motility, biofilm formation, and bacterial adhesion and suggest an effective chemical approach to control intertwined signaling processes that are important for biofilm formation and motilities. Abstract : Upwardly motile : Disaccharides derivatized with saturated farnesol dominate the activity of rhamnolipids naturally secreted by P. aeruginosa at activating and inhibiting the swarming motilities. The results identified important structural elements for controlling swarming motility as well as biofilm formation, and bacterial adhesion.